Peran Kegiatan Ekstrakurikuler Dalam Pembinaan Dan Pengembangan Siswa Sekolah Dasar - Intan Oktaviani Agustina; Juliantika Juliantika; Selly Ade Saputri; Syahla Rizkia Putri N (Jurnal Bintang Pendidikan Indonesia, 2023)
The role of extracurricular activities in the guidance and development of students in elementary schools is very important in providing a holistic and in-depth learning experience outside the ordinary academic environment. The purpose of this study was to find out the role of extracurriculars in fostering and developing students at SD 186 Cipadung and SD Al-Ma'soem. This study uses a qualitative method that produces and processes descriptive data such as interview transcripts. The results of this study show that extracurricular roles instill character values ​​such as hard work, discipline, teamwork, leadership, and responsibility. In addition, extracurricular roles can develop students' potential interests and talents.